PET imaging of HIV-1 envelope protein gp120 using 18F-labeled nanobodies - Neysha Martinez-Orengo; Swati Shah; Jianhao Lai; Falguni Basuli; Anna Lyndaker; Mitchell L. Turner; Morteza Peiravi; Suman Sourabh; Kevon Sampson; Peng Zhang; Rolf E. Swenson; Paolo Lusso; et al. (iScience)
Summary: Radiolabeled antibodies against the HIV-1 envelope protein, gp120, have been previously tested in animal models and in people with HIV (PWH). Nanobodies offer advantages over antibodies, including smaller size and faster clearance, which allow labeling with fluorine-18. In this study, three nanobodies (J3, 3E3, B9) chosen based on their binding properties to the conserved CD4-binding site of gp120 were labeled with fluorine-18 and used for PET imaging in mice bearing wild-type (WT) and/or gp120-expressing (Env+) tumors. [18F]J3 and [18F]3E3 selectively targeted Env+ tumors and not WT tumors, with minimal background signal. Switching from non-site-specific radiolabeling method to sortase A-mediated site-specific conjugation at the C-terminus improved binding to Env+ tumors for all nanobodies. Site-specifically 18F-labeled J3 nanobody is the most promising candidate with the highest level of binding. These results establish an Env+ imaging method that will enable next stage testing in an HIV-1 preclinical infection model and potentially in PWH.